Jemimah Njuki looks to an inclusive future for small-holder farming in Africa - Njuki, Jemimah (Future Agricultures Consortium, 2020)
In the third of a four-part blog series following the UN Sustainable Development Solutions Network, Foresight4Food, IFAD and APRA eDialogue session on the future of small-scale farming, Jemimah Njuki, the International Food Policy Research Institute’s Director for Africa, reflects on the discussion and emphasises the importance of this sector’s social dimensions.